Higher hazard of concussion combined with recurrent concussion in female youth ice hockey compared with males: An opportunity for concussion prevention - Eliason, P.; Galarneau, j.-M.; Schneider, K.; Babul, S.; Mrazik, M.; Lebrun, C.; Hagel, B.; Emery, C. (Sport-Orthopädie - Sport-Traumatologie, 2023)
Summary Background: Ice hockey is a popular sport globally with growing participation for boys and girls, yet remains a high-risk sport for concussion and recurrent concussion. The purpose of this study was to examine the associations of several potential factors and the hazard of first in-season concussion combined with recurrent concussion, among Canadian youth ice hockey players. Material and Methods: A prospective cohort study was conducted over 5 seasons of play (2013-2018) in Canadian youth ice hockey players (males and females; ages 11-18years). All concussions were ice hockey-related and diagnosed by a physician. Concussion outcome was examined by combining first in-season and recurrent concussion if more than one was sustained within the same season. A multiple failure time Cox regression adjusting for clustering by player was used to examine potential factors associated with concussion combined with recurrent concussion. Results: A combined total 6549 player-seasons were included. There were 454 first in-season concussions and 22 recurrent concussions. Crude rates combining first and recurrent concussion were 5.15/1000 exposure-weeks (95% CI: 3.88-6.83) for females participating in female-only leagues, 3.65/1000 exposure-weeks (95% CI: 2.07-6.43) for females participating in mixed leagues (predominately male-based teams), and 3.67/1000 exposure-weeks (95% CI: 3.33-4.04) for males participating in mixed leagues. Results of the final Cox model demonstrated that females playing in female-only leagues were 2.65 times more likely to sustain a concussion relative to male players participating in mixed leagues (hazard ratio (HR) = 2.65; 95% CI: 1.76-3.99). Other factors increasing hazard for first in-season concussion combined with recurrent concussion included policy permitting body checking (HR = 2.02; 95% CI: 1.47-2.78), having a preseason history of injury within the previous 12 months (HR = 1.28; 95% CI: 1.02-1.62) or lifetime concussion (HR = 1.52; 95% CI: 1.24-1.87), playing in a sub-elite (lower) level of play (HR = 1.35; 95% CI: 1.07-1.69), playing forward (HR = 1.57; 95% CI: 1.06-2.33) or defence (HR = 1.63; 95% CI: 1.09-2.46) relative to goaltenders. Self-report of never wearing a mouthguard (HR = 1.16; 95% CI: 0.91-1.47) was not statistically significant but may have clinical relevance in informing concussion prevention. Conclusions: Several factors associated with a higher hazard of first in-season concussion combined with recurrent concussion in youth ice hockey were noted. These results will continue to inform relevant concussion prevention strategies. Future research in female-only youth ice hockey leagues should be a focus to inform primary and secondary prevention strategies in this high risk population.